Anna Madgigine Jai Kingsley : African princess, Florida slave, plantation slaveowner - Schafer, Daniel L. (Gainesville : University Press of Florida, 2003)
Anna Kingsley's life story adds a dramatic chapter to histories of the South, the state of Florida, and the African Diaspora. Both an American slave and a slaveowner and possibly an African princess. Anna was captured as a teenager in Senegal in 1806 and sold into slavery. Zephaniah Kingsley, Jr., a planter and slave trader from Spanish East Florida, bought her in Havana and took her to his St. Johns River plantation, where she soon became his household manager, his wife, and eventually the mother of four of his children.
Senegal: Anta Majigeen N diaye -- Havana: Zephaniah Kingsley, Jr. -- Laurel Grove: Anna Madgigine Jai Kingsley -- The Patriot War -- Fort George Island -- Refuge in Haiti and return to Florida -- A free Black community in a time of race hysteria -- Final Flight: The American Civil War -- Final years -- A personal postscript -- Appendix: The last will and testament of Anna Madgigine Jai Kingsley.
Includes bibliographical references (pages 155-167) and index.
Charlton Tebeau Book Award (Florida Historical Society), 2004
NLJCols20082021
Keywords: Kingsley, Anna, -- 1793-1870.; Kingsley family; Kingsley, Anna Madgigine Jai; Kingsley (Family); Kingsley, Anna, -- 1793-1870; Kingsley family; Kingsley; Ndiaye; Baxter; Gibbs; McNeill; Mocs; Sammis; Kingsley, Anna Madgigine Jai, -- ca1793-1870.; Kingsley , -- fam; Women slaves -- Florida -- Fort George Island -- Biography; Slaves -- Florida -- Fort George Island -- Biography; Princesses -- Senegal -- Biography; Women plantation owners -- Florida -- Fort George Island -- Biography; African American women -- Florida -- Fort George Island -- Biography; Plantation life -- Florida -- Fort George Island; Fort George Island (Fla.) -- Biography; Senegal -- Biography; 15.80 history of Africa; 15.85 history of America; African American women; Plantation life; Princesses; Slaves; Women plantation owners; Women slaves; Florida -- Fort George Island; Senegal; African Americans -- Florida; Slaves -- United States -- Biography; Negers; Slavernij; Plantages; Biographies; Biographies (form); Biographies